Comparing the prognostic value of risk stratifying models for patients with lower‐risk myelodysplastic syndromes: Is one model better?. Issue 11 (November 2015) - Zeidan, Amer M.; Sekeres, Mikkael A.; Wang, Xiao‐Feng; Al Ali, Najla; Garcia‐Manero, Guillermo; Steensma, David P.; Roboz, Gail; Barnard, John; Padron, Eric; DeZern, Amy; Maciejewski, Jaroslaw P.; List, Alan F.; et al.
<x xml:space="preserve">Abstract</x> Some patients classified as having lower‐risk (LR)‐disease by the International Prognostic Scoring System (IPSS) fare more poorly than predicted. We examined the prognostic utility of IPSS, the MD Anderson LR‐Prognostic System (LR‐PSS), and the revised IPSS (IPSS‐R) in a large cohort of patients classified as having IPSS LR‐MDS in the MDS Clinical Research Consortium database. Actual overall survival (OS) was assessed in patients with IPSS LR‐MDS (i.e. low and intermediate‐1) using Kaplan–Meier methods. Harrell's c index (HCI) and Akaike information criteria (AIC) were used to compare the models. Median OS of 1, 140 eligible patients was 47 months (95% CI, 44–52). Median follow‐up was 62 months. HCI values indicating the discriminatory power of the models (higher is better) were better for LR‐PSS (0.74, 95% CI, 0.70–0.78) than IPSS‐R (0.64, 95% CI, 0.60–0.67) and IPSS (0.64, 95% CI, 0.60–0.68). Similarly, AIC values indicating the goodness of the fit were better for LR‐PSS than IPSS‐R and IPSS (8, 110, 8, 147, and 8, 150, respectively, lower is better). LR‐PSS assigned 25.1% and 37.4% of patients with IPSS LR‐MDS into LR‐PSS Category 3 and IPSS‐R Categories ≥Intermediate, respectively. Of 291 patients (25.5%) who survived ≤24 months from diagnosis, only 37.1% and 45% were classified as LR‐PSS category 3 and IPSS‐R categories ≥Intermediate, respectively (P = 0.06). While both LR‐PSS and IPSS‐R distinguish groups with varied survival outcome among patients with IPSS LR‐MDS, both tools fail to identify a significant subset with poor OS. Future studies should assess whether patients identified as at increased risk will benefit from earlier interventions with disease‐modifying therapies. Am. J. Hematol. 90:1036–1040, 2015. © 2015 Wiley Periodicals, Inc.